Digital approaches to intercultural competence in higher education—a PRISMA systematic review with bibliometric and SWiM evidence - Naranjo-Toro, Miguel; Basantes-Andrade, Andrea; Meneses, Mónica; Guerra, Julio (Frontiers in Education, 2026)
Digital internationalization has moved beyond “mobility-at-a-distance” toward course-embedded designs that can scale intercultural competence (IC) development. Using PRISMA, we mapped digital technologies and pedagogical strategies used to teach IC in higher education, outcome measures, direction of effects, and equity-related implementation conditions, and we added mechanism-oriented coding linking modality affordances to learning processes and IC outcomes. We searched Scopus, Web of Science, and ERIC and screened 133 records. Twenty-four studies (total n = 1,787) met eligibility criteria. We combined descriptive bibliometrics with an adapted JBI quality appraisal (median quality 78.6%, IQR 57.1–85.7), a SWiM synthesis of effect direction by strategy, and intervention-level mechanism coding. Evidence clusters around LMS/forums, videoconferencing and collaboration suites, immersive VR/360°, telepresence/telesimulation, MOOCs, and guided inquiry. Across modalities, the most consistent IC gains occur when interventions instantiate structured intercultural contact, facilitation and feedback, authentic co-production, and guided reflection/debriefing. Scenario-based and immersive formats are most effective when situated performance is paired with structured debriefing and feedback. By contrast, content-centric LMS/MOOC formats show mixed results unless instructors engineer dialogic tasks and active facilitation to convert exposure into interaction. Most studies rely on standardized self-report measures; performance or observational evidence is less common and concentrates in simulation and role-play contexts. Reported constraints include connectivity, language and time-zone barriers, and facilitation workload, underscoring the role of institutional support. Future research should strengthen comparative and longitudinal designs, report implementation fidelity and dosage, validate instruments across languages, and triangulate self-report with performance evidence and downstream academic/employability outcomes.